2013
DOI: 10.1097/rlu.0b013e318279b9df
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time-of-Flight and Point-Spread-Function in SUV Quantification for Oncological PET

Abstract: SUV(50) provides accurate quantification and should replace SUV(max) in PET tomographs incorporating advanced reconstruction techniques. PSF + TOF reconstruction is the optimum for both detection and accurate quantification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 11 publications
6
43
0
Order By: Relevance
“…Results obtained for ROI definition agreed with the results obtained by Prieto et al [3] and Ronald et al [6], SUV peak and SUV 50 showed less variation with reconstruction methods than SUV max and these ROIs could be used to evaluate the stage and treatment response. However, it must be considered that SUV 50 shows a great dependence on …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Results obtained for ROI definition agreed with the results obtained by Prieto et al [3] and Ronald et al [6], SUV peak and SUV 50 showed less variation with reconstruction methods than SUV max and these ROIs could be used to evaluate the stage and treatment response. However, it must be considered that SUV 50 shows a great dependence on …”
Section: Discussionsupporting
confidence: 80%
“…SUV quantification depends on the election of filters, iteration numbers, full width at half maximum (FWHM), and subset. Time-of-flight (TOF) and point-spread-function (PSF) are recent reconstruction algorithms that have been suggested to further improve the accuracy of SUV quantification [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that SUVs are highly dependent on scanner resolution and image reconstruction techniques and may differ significantly between departments [46]. Absolute values of uptake in normal tissues of the different tracers are therefore difficult to compare unless performed by the same department, and no such data exist in the literature.…”
Section: Somatostatin Receptor Tracer Affinitymentioning
confidence: 99%
“…This optimization has already been investigated for oncological PET [7][8][9]. Nevertheless, few investigations have focused in the field of brain PET [10] and a standard reconstruction protocol has not been established yet.…”
Section: Introductionmentioning
confidence: 99%